1993
DOI: 10.1083/jcb.123.6.1821
|View full text |Cite
|
Sign up to set email alerts
|

The SLT2 (MPK1) MAP kinase homolog is involved in polarized cell growth in Saccharomyces cerevisiae.

Abstract: Abstract. Bud emergence, spindle pole body duplication and DNA replication are all dependent on the activation of the CDC28 protein kinase at the Start point in the G1 phase of the cell cycle. Bud emergence requires polarization of the cytoskeleton and secretory vesicles to a specific site on the cell surface. Cdc28p activated by Gl-cyclins triggers polarization of actin to the site of bud emergence and favors apical bud growth (Lew, D. J., and S. I. Reed. 1993. J. Cell Biol. 120:1305-1320 C ELL reproduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
180
0
1

Year Published

1995
1995
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(191 citation statements)
references
References 68 publications
(117 reference statements)
10
180
0
1
Order By: Relevance
“…Two independent trans- Effects of MKC1 deletion on sensitivities to high temperature and caffeine. SLT2 function in S. cerevisiae is required for viability of growing cells at 37ЊC, but not at 24ЊC (38,45,66). Lysis at the nonpermissive temperature is prevented by osmotic stabilization with 1 M sorbitol.…”
Section: Resultsmentioning
confidence: 99%
“…Two independent trans- Effects of MKC1 deletion on sensitivities to high temperature and caffeine. SLT2 function in S. cerevisiae is required for viability of growing cells at 37ЊC, but not at 24ЊC (38,45,66). Lysis at the nonpermissive temperature is prevented by osmotic stabilization with 1 M sorbitol.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that some phenotypes are generally more evident in homozygous diploid mutant strains than in haploid mutant strains (Johnston et al, 1991;Liu and Bretscher, 1992;Mazzoni et al, 1993). For this reason, we constructed an homozygous Kllsm4D::KanMX4/Kllsm4D:: KanMX4 diploid strain (CMK42) and studied the effects of the double mutation in this strain.…”
Section: Phenotypic Consequences Of Kllsm4d::kanmx4 Disruptionmentioning
confidence: 99%
“…In addition, a mutation in MPK1 was isolated in a search for mutations that enhance the growth defect of a temperature-sensitive allele of the CDC28 cell cycle gene (Mazzoni et al 1993), further suggesting that the cell cycle engine plays a role in cell wall construction. However, measurements of MPK1 activity in synchronized cells have failed to reveal fluctuations through the cell cycle (Y. Kamada and D.E.…”
Section: Other Signals That Lead To Activation Of Pkc1mentioning
confidence: 99%